Tuning of magnetic properties and giant magnetoimpedance effect in multilayered microwires - R. López Antón; J.P. Andrés; J.A. González; A. García-Gómez; V. Zhukova; A. Chizhik; M. Salaheldeen; A. Zhukov (Journal of Science: Advanced Materials and Devices, 2024)
We studied the magnetic properties and Giant Magnetoimpedance (GMI) effect in amorphous Co-rich microwires with similar chemical compositions and different diameters with magnetic (Co, Permalloy) and non-magnetic (Cu) layers deposited by magnetic sputtering onto glass-coating. Studies of magnetic properties and GMI effect of as-prepared microwires and the same microwires with deposited magnetic and non-magnetic layers reveal substantial impact of such layers on GMI effect and hysteresis loops. Both as-prepared samples present soft magnetic properties and high GMI effect. The contribution of magnetic layers is observed in hysteresis loop at higher magnetic field, with hysteresis loops similar to those observed in microwires with mixed amorphous-crystalline structure. Meanwhile, both magnetic and non-magnetic layers affect low field hysteresis loops of both samples. Additionally, the GMI ratio, ΔZ/Z, and magnetic field dependences of GMI ratio are substantially affected by the presence of magnetic and non-magnetic layers deposited onto glass-coating. We discussed the observed experimental dependences considering both change of the internal stresses originated by the sputtered layer as well as the magnetostatic interaction between the amorphous ferromagnetic nucleus and deposited magnetic layers.